Relationship between apoptosis and survival molecules in human cumulus cells as markers of oocyte competence. Issue 5 (8th August 2017) - Bosco, Liana; Chiarelli, Roberto; Roccheri, Maria Carmela; Matranga, Domenica; Ruvolo, Giovanni
Summary: To select from a single patient the best oocytes able to reach the blastocyst stage, we searched for valuable markers for oocytes competence. We evaluated the DNA fragmentation index (DFI) and the level of some survival molecules, such as AKT, pAKT and pERK1/2, in individual cumulus cell–oocyte complexes (COC). The study included normo-responder women. The average age of the patients was 34.3. DFI in cumulus cells was evaluated using the terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labelling (TUNEL) assay in situ . AKT, pAKT and pERK1/2 were measured by immunological assay and densitometric analysis of fluorescent signals using NIS-Elements BR 3.10 image software. Statistical analysis was performed using STATA SE/14.1. The study focused on 53 patients involved after informed consent. Out of 255 MII oocytes, 197 were fertilized and the derived embryos had the following evolution: 117 completed the development to blastocyst and were transferred to uterus; 57 were vitrified at the blastocyst stage; and 23 were arrested during in vitro culture at different stages of cleavage. We found a significant statistical difference between the DFI of cumulus cells of the arrested embryos and the transferred blastocysts ( P = 0.004), confirming that DFI could be considered as a valuable marker of oocyte competence. In addition, the pAKT/DFI ratio was higher in cumulus cells of oocytes able to produce blastocysts, indicating that DFI is significantly lower when pAKT is higher ( P = 0.043). This study demonstrates for the first time that the relationship between apoptosis and survival molecules can be used as a marker to select the best oocytes.